Effect of boiling time on protein content, total soluble solids, and sensory quality of probiotic soy milk (Glycine max L.). - Faisal, Muhammad; Hafasa, Hafasa; Malika Azizatul FItri M, Siti; Kusumaningtyas, Maharani (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
This study aimed to analyze the effect of different boiling time on protein content, total soluble solids (TSS), and sensory characteristics, including taste and aroma, of probiotic soy milk (Glycine max L.). The experiment was conducted using a Completely Randomized Design (CRD) consisting of four boiling time treatments of 5, 10, 15, and 20 minutes, each replicated three times, resulting in a total of 18 experimental units. The observed parameters included protein content, total soluble solids (TSS), and sensory evaluation performed by trained panelists using a hedonic test (five-point scale). Scores ranged from 1 (“dislike extremely”) to 5 (“like extremely”), where higher values indicated greater sensory preference. The collected data were statistically analyzed using Analysis of Variance (ANOVA), and when a significant difference was observed (p < 0.05), the analysis was continued with Duncan’s Multiple Range Test (DMRT) at a 5% confidence level. Data processing was performed using SPSS version 25. The results showed that boiling time had a significant effect on protein content, total soluble solids, and hedonic scores for taste and aroma attributes. The 15-minute boiling treatment produced the highest protein content (3.11%), optimal TSS value (8.9 °Brix), and the highest acceptance scores for both taste and aroma. Therefore, boiling at 95–100°C for 15 minutes can be considered the optimal condition to produce probiotic soy milk with the best balance between protein stability, total soluble solids concentration, and sensory quality.